The Urgency of Critical Thinking Character for Elementry Student - Mubarok, Husni; Anggraini, Dian Mustika; Charis, Abdul (Pascasarjana IAIN Kudus, 2023)
Critical thinking competence for students is crucial throughout the learning process in the classroom so that students are accustomed to using reasoning systems to solve problems faced by students. This study aims to explain how to improve the ability to think critically in elementary school students. This research uses library research. The method used in research is literature study. Several stages in literature study research are data collection, reduction, presentation, and conclusion. There are many ways to improve critical abilities in elementary schools, including fostering and growing critical thinking in every lesson. Critical thinking skills can be started by conditioning the learning atmosphere by asking each other questions, discussing an object, and analyzing the material to be discussed. So, student’s critical thinking skills are also influenced by learning styles at school, starting from the teacher's teaching methods and style, facilities, and student feedback on the lessons being taught. Urgensi Karakter Berpikir Kritis Bagi Siswa Sekolah Dasar. Kompetensi berpikir kritis bagi siswa sangat penting dilakukan melalui proses pembelajaran di kelas sehingga siswa terbiasa menggunakan sistem bernalar untuk memecahkan masalah yang dihadapi siswa. Tujuan penelitian ini yaitu menjelaskan cara meningkatkan kemampun berpikir kritis pada siswa sekolah dasar. Penelitian yang ini menggunakan penelitian kepustakaan. Metode yang digunakan dalam penelitian adalah studi pustaka. Beberapa tahapan dalam penelitian studi pustaka yaitu pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Upaya cara untuk meningkatkan kemampuan kritis sekolah dasar, salah satunya dengan memupuk dan menumbuhkan pemikiran kritis pada setiap pembelajaran. Kemampuan berpikir kritis dapat dimulai dengan mengkondisikan suasana pembelajaran dengan memberikan pertanyaan atau saling bertanya jawab, mendiskusikan sebuah objek, dan menganalisis tentang materi yang akan dibahas. Jadi, kemampuan berfikir kritis siswa juga dipengaruhi oleh gaya belajar di sekolah, mulai dari metode dan gaya mengajar guru, fasilitas, dan umpan balik siswa terhadap pelajaran yang diajarkan.